INISIASI PENGEMBANGAN DESA NGESREPBALONG SEBAGAI SENTRA ALPUKAT BERBASIS GREEN ECONOMY DI KABUPATEN KENDAL, JAWA TENGAH - Retnoningsih, Amin; Ngabiyanto, Ngabiyanto; Triwibowo, Bayu; Hadiyanti, Luthfia Nur; Solichin, Solichin; Laraswati, Vivi Anggraeni; Rizki, Angela Dita; Sa’adah, Nur (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2024)
The initiation of the development of Ngesrepbalong Village as a green economy-based avocado center is supported by the village's regional conditions. A green economy needs to be implemented because Ngesrepbalong is known to be the only village in Kendal Regency that has the potential for landslides. Landslide mitigation can be done by increasing the population of deep-rooted, compact, and massive woody trees such as avocados so that water can be retained and the soil becomes stable. The priority problems of the Gunungsari farmer partners in Ngesrepbalong Village include management and production aspects of preparing their area as an avocado center area. Farmer group institutions have yet to be available, and most avocados are not superior varieties. This activity aims to initiate Ngesrepbalong as a green economy-based avocado center. Activities will occur in May-November 2023 through socialization, training and mentoring, application of technology and mentoring, monitoring and evaluation, and sustainability program. The institution of superior avocado farmers was realized by forming the "Gunung Berkah" avocado farmer group. Facilities and infrastructure such as seedling houses, grafting knives, and others were used to propagate 300 seedlings, and top working on 15 adult avocado trees. The superior variety of trees used for grafting and TW is Diane avocado. Increased empowerment of farmer partners is measured after program implementation. The results of measuring the cognitive, psychomotor, and affective/enthusiasm aspects via questionnaires showed the highest to lowest increases in the affective/enthusiasm, cognitive, and psychomotor aspects, respectively. The availability of grafting and TW facilities and infrastructure, as well as increasing farmers' abilities in these three aspects, is a manifestation of the achievements of the initiation of Ngesrepbalong Village to become a superior avocado center based on a green economy.Inisiasi pengembangan Desa Ngesrepbalong sebagai sentra alpukat berbasis green economy didukung kondisi kewilayahan desa. Green economy perlu diterapkan karena Ngesrepbalong diketahui sebagai satu-satunya desa di Kabupaten Kendal yang berpotensi longsor. Mitigasi longsor dapat dilakukan melalui peningkatan populasi pohon berkayu berakar dalam, kompak, dan masif seperti alpukat sehingga air dapat ditahan dan tanah menjadi stabil. Permasalahan prioritas mitra petani Dusun Gunungsari di Desa Ngesrepbalong meliputi aspek manajemen dan produksi dalam rangka menyiapkan wilayahnya sebagai kawasan sentra alpukat. Kelembagaan kelompok tani belum tersedia dan sebagaian besar alpukat bukan varietas unggul. Tujuan kegiatan ini menginisiasi Ngesrepbalong sebagai sentra alpukat berbasis green economy. Kegiatan berlangsung Mei-November 2023 melalui tahapan sosialisasi, pelatihan dan pendampingan, penerapan teknolog dan pendampingan, monitoring dan evaluasi, serta keberlanjutan program. Kelembagaan petani alpukat unggul direalisasikan melalui pembentukan kelompok tani alpukat “Gunung Berkah”. Sarana dan prasarana seperti rumah bibit, pisau grafting dan lainnya digunakan dalam perbanyakan grafting sebanyak 300 bibit, dan top working pada 15 pohon alpukat dewasa. Entres varietas unggul yang digunakan untuk grafting dan TW tersebut adalah alpukat Diane. Peningkatan keberdayaan mitra petani diukur sesudah pelaksanaan program.  Hasil pengukuran aspek kognitif, psikomotor, dan afektif/antusiame melalui kuesioner menunjukkan peningkatan tertinggi hingga terendah berturut-turut adalah aspek afektif/antusiame, kognitif, dan psikomotor. Ketersediaan sarana dan prasarana grafting dan TW serta peningkatan kemampuan petani pada ketiga aspek tersebut  merupakan wujud capaian inisiasi Desa Ngesrepbalong menjadi sentra alpukat unggul berbasis green economy.